The psychopathic manager behaviour and the employee workplace deviance: the mediating role of revenge motive; the moderating roles of core self-evaluations and attitude ımportance - Bulkan, Sinem (My University, 2017)
Bu araştırma, psikopatik yönetici davranışı kavramını oluşturmayı ve psikopatik yönetici davranışı ölçeğini geliştirmeyi amaçlamaktadır. Araştırma ayrıca psikopatik yönetici davranışı ve işyerinde sapkın davranış arasındaki ilişkiyi, intikam niyeti kavramını ara değişken; temel benlik (

benlik) değerlendirmeleri ve tutumun önemi kavramlarını şartlı değişken olarak ele alıp açıklamayı hedeflemektedir.Araştırma verileri, çeşitli mesleklerde ve sektörlerde bir yöneticiye bağlı olarak çalışan ya da daha önceden çalışmış 519 kişilik bir örneklem grubundan Türkiye’de toplanmıştır. Psikopatik yönetici davranışı ölçeği önerilen on boyuttan farklı olarak beş boyut olarak sonuçlanmıştır. Hipotezleri test etmek için basit doğrusal ve hiyerarşik regresyon analizleri uygulanmıştır. ABSTRACT To the author’s knowledge, this is the first study which introduces the construct of the psychopathic manager behaviour and aims for the development of the psychopathic manager behaviour (Psycho-Man B) measure. The study also aims for the understanding of the relationship between the psychopathic manager behaviour and the workplace deviance while investigating the mediating role of the revenge motive and the moderating roles of the core self-evaluations and the attitude importance.Data were collected from 519 employees from a wide variety of jobs and industries who currently work for or previously worked for a manager in a collectivist culture, Turkey. Psycho-Man B Measure was developed resulting in five dimensions as opposed to the proposed ten dimensions. Simple linear and hierarchical regression analyses were conducted to test the hypotheses.
Keywords: attitude importance; core self-evaluations; İşletme; işyerinde sapkın davranış; organisation-directed deviance; örgüte karşı intikam niyeti; örgüte yönelik sapkın davranış; Örgütsel davranış; psikopatik yönetici davranışı; psychopathic manager behaviour; revenge motive towards the manager; revenge motive towards the organisation; supervisor-directed deviance; temel benlik (öz benlik) değerlendirmeleri; tutumun önemi; workplace deviance; yöneticiye karşı intikam niyeti; yöneticiye yönelik sapkın davranış; Yönetim